Statecraft and classical learning: the rituals of Zhou in East Asian history - Elman, Benjamin A. (Brill, 2010)
Introduction / Benjamin A. Elman and Martin Kern -- Part I. Early China -- The Zhouli as constitutional text / David Schaberg -- Offices of writing and reading in the Rituals of Zhou / Martin Kern -- The many Dukes of Zhou in early sources / Michael Nylan -- Centering the realm: Wang Mang, the Zhouli, and early Chinese statecraft / Michael Puett -- Zheng Xuan's commentary on the Zhouli / Andrew H. Plaks -- Part II. Medieval China -- The role of the Zhouli in seventh- and eighth-century administrative traditions / David McMullen -- Wang Anshi and the Zhouli / Peter K. Bol -- Tension and balance: changes of constitutional schemes in Southern Song commentaries on the rituals of Zhou / Jaeyoon Song -- Part III. Early modern East Asia -- Tokugawa approaches to the Rituals of Zhou: the late Mito School and "feudalism" / Kate Wildman Nakai -- Yun Hyu and the search for dominance: a seventeenth-century Korean reading of the Offices of Zhou and the Rituals of Zhou / Jahyun Kim Haboush -- The story of a chapter: changing views of the "Artificer's Record" ("Kaogong ji") and the Zhouli / Benjamin A. Elman -- Part IV. Modern China -- The Zhouli as the late Qing path to the future / Rudolf G. Wagner -- Denouement: some conclusions about the Zhouli / Rudolf G. Wagner
Includes bibliographical references and index. - This volume received support from the "New perspectives in Chinese culture and society" program, which is made possible by a grant from the Chiang Ching-kuo Fondation for International Scholarly Exchange to the American Council of Learned Societies
Keywords: Zhou li; China -- Politics and government; East Asia -- Politics and government; Aufsatzsammlung; Zhouli